Twenty‐year experience of paediatric thyroid surgery using intraoperative nerve monitoring. Issue 8 (13th March 2018) - Schneider, R.; Machens, A.; Sekulla, C.; Lorenz, K.; Weber, F.; Dralle, H.
Abstract : Background: There are few data on intermittent and continuous intraoperative nerve monitoring (IONM) during thyroidectomy in children. Methods: All children aged 18 years or younger who had standard thyroid operations using intermittent or continuous IONM between January 1998 and December 2016 were included in the study. The impact of age and type of IONM on basal amplitude, latency and complications after thyroidectomy were assessed. Results: A total of 504 children were included in the study. With continuous IONM, median basal amplitude and latency increased significantly with age, more on the left side (from 199 to 870 μV, and from 3·88 to 5·75 ms) than on the right (from 340 to 778 μV, and from 2·63 to 3·50 ms). Compared with intermittent IONM with needle electrode, continuous IONM with tube electrode resulted in an increase in median basal amplitude in children aged 13–18 years on both sides (from 675 to 778 μV on the right and from 450 to 870 μV on the left), and a decrease in median latency in all children older than 3 years: in children aged 4–6 years, from 4·20 to 3·00 ms on the right and from 6·10 to 4·63 ms on the left; in children aged 7–12 years, from 4·60 to 3·50 ms and from 6·00 to 5·25 ms respectively; and in children aged 13–18 years, from 4·60 to 3·50 ms and from 6·40 to 5·75 ms. Overall, wound infection, but not bleeding/haematoma or vocal fold palsy, affected younger children more: 3 per cent of children aged 3 years or less; 2 per cent of children aged 4–6 years; and 0 per cent of children aged over 6 years ( P  = 0·031). With continuous IONM, no wound infection, bleeding/haematoma or permanent vocal fold palsy was noted in any age group. Conclusion: Continuous IONM measures nerve electrophysiology more accurately than intermittent IONM during thyroidectomy in children. Abstract : Smaller tools needed